THE URGENCY OF SPIRITUAL EDUCATION IN FACING SOCIETY PERSPECTIVE Dr. KH. SAID AQIL SIRAJ IN HIS BOOK TASAWUF AS A SOCIAL CRITICISM - Muhammad Arif Nasruddin, Qowiyudin Mulya Lubis, Hasan Bisri (JIPI (Jurnal Ilmiah Pendidikan Islam), 2025)
This research is based on the phenomenon that occurs in modern society, which is not only experiencing a crisis of purpose or spiritual emptiness. Therefore, the author provides his study that examines the need for spiritual education in interacting with society from the perspective of Dr. KH.Said Aqil Siraj in his book "Sufism as Social Criticism". The main purpose of spiritual education in general is to empower the individual self which refers to the development of a harmonious relationship with God (Hablun Minallah), others (Hablun Minannaas) and the universe (Hablun Minalkaun) by following the instructions of the Prophet, as well as spiritual education as the processing of the human soul in developing moral character. This research uses library research, the researcher uses sources of information in the literature and relevant documents to answer research questions or examine the hypotheses proposed. This method involves searching, selecting, and critically analyzing the existing literature to gain a deeper understanding of the topic being researched. The essence is how individuals adapt and position themselves as best they can in interactions with all of them and with anyone. In essence, everything in life involves an educational component because of the interaction with the environment. Like existing societies, in reality the burgeoning educational culture is still too focused on academic meanings, intelligence, and perhaps tied to the adjective, "rarely" aimed at emotional and spiritual intelligence. At its core is how individuals adapt and position themselves as best as possible in interactions with all conditions and with anyone. In essence, everything in life involves an educational component because of the interaction with the environment